Tantangan Kepemimpinan Kepala Sekolah Visioner dalam Memahami Visi Misi Sekolah - Fadilah, Ahmad Arif; Nabila, Aida; Apriliani, Aira; Rahma, Dinda Aliya; Fitri, Indah Zianira; Rohmah, Nafisah Nur; Kumarani, Nanda Citra; Setiawan, Rangga Rizky; Umma, Siti Azkiatul; Julianis, Tania (Lembaga Yasin AlSys, 2022)
This study aims to determine how much influence the principal's visionary leadership has on the management of the school's vision and mission at SDI DAARUL HUDA in Jati Uwung, Banten. This research uses a literature study approach or can be called library research, with qualitative methods. Through research from various journals, it shows that the visionary leadership of the principal is an important factor that must be built together in an effort to achieve the management of the school's vision and mission, so that the synergy of the visionary leadership of the principal is expected to improve the vision and mission in elementary schools.